Hepatocellular carcinoma complicated with huge posterior pancreas head lymph node metastasis and primary renal carcinoma: A case report - Chen, Jun; Zhou, Zhiyi; Chen, Wenyan; Khan, Abid Ali; Liu, Zhikun; Wang, Kai; Yang, Fan; Xu, Xiao (Frontiers in Oncology, 2022)
The incidence of hepatocellular carcinoma (HCC) associated with extrahepatic primary malignancy (EHPM) is extremely rare, especially for those that involve primary renal cell carcinoma (PRC). Here we present a case of a 66-year-old male who was diagnosed with HCC complicated with lymph node metastasis at posterior pancreas head and PRC. Biopsy results of the liver and the lymph node confirmed the diagnosis of HCC. The disease progressions of both HCC and PRC are controlled effectively following the initiation of comprehensive therapy including pembrolizumab, lenvatinib, radiotherapy, and transcatheter arterial chemo-embolization (TACE). Ultimately, the patient had successfully access to surgery and complete response (CR) of all the tumors were achieved after surgery.